2019
DOI: 10.1158/1541-7786.mcr-19-0264
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Morphological Phenotype in Chemoresistant Triple-Negative Breast Cancer Reveals Metabolic Reprogramming and PLIN4 Expression as a Molecular Vulnerability

Abstract: The major obstacle in successfully treating triple-negative breast cancer (TNBC) is resistance to cytotoxic chemotherapy, the mainstay of treatment in this disease. Previous preclinical models of chemoresistance in TNBC have suffered from a lack of clinical relevance. Using a single high dose chemotherapy treatment, we developed a novel MDA-MB-436 cell-based model of chemoresistance characterized by a unique and complex morphologic phenotype, which consists of polyploid giant cancer cells giving rise to neuron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 66 publications
3
66
0
4
Order By: Relevance
“…Consistent with these properties, a significant number of recent reports with different biological systems (e.g., tumor-derived cell lines, animal models, and specimens from cancer patients) have underscored the key roles played by PGCCs in tumorigenesis, metastasis, and disease relapse after conventional cancer treatments. The contributions that PGCCs make to therapy resistance is demonstrated for various types of solid tumors, including ovarian cancer [43,44], prostate cancer [23,47], brain cancer [26,28], renal cancer [54], colon cancer [46], and breast cancer [45,55], including the most aggressive form (triple negative) [55] for which chemotherapy remains the cornerstone therapeutic. There have been several reviews on the formation, stemness, and tumorigenicity of PGCCs before and after exposure to cancer therapeutic agents (e.g., [56][57][58][59]).…”
Section: Multinucleated/polyploid Cancer Cellsmentioning
confidence: 99%
“…Consistent with these properties, a significant number of recent reports with different biological systems (e.g., tumor-derived cell lines, animal models, and specimens from cancer patients) have underscored the key roles played by PGCCs in tumorigenesis, metastasis, and disease relapse after conventional cancer treatments. The contributions that PGCCs make to therapy resistance is demonstrated for various types of solid tumors, including ovarian cancer [43,44], prostate cancer [23,47], brain cancer [26,28], renal cancer [54], colon cancer [46], and breast cancer [45,55], including the most aggressive form (triple negative) [55] for which chemotherapy remains the cornerstone therapeutic. There have been several reviews on the formation, stemness, and tumorigenicity of PGCCs before and after exposure to cancer therapeutic agents (e.g., [56][57][58][59]).…”
Section: Multinucleated/polyploid Cancer Cellsmentioning
confidence: 99%
“…PLIN1 may affect tumor progression through PPARG/PPAR γ pathway in breast cancer [ 69 ]. At the same time, another member of the same family, PLIN4, has also been identified as a therapeutic target for triple-negative breast cancer [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, docetaxel-resistant prostate cancer was shown to shunt several metabolic intermediates, namely lactate, glutamine, and glucose towards OXPHOS, with a concomitant decrease in intracellular ROS content [247]. Furthermore, doxorubicin resistance in a primary triple-negative breast cancer cell line was shown to be achieved through the OXPHOS upregulation, with a parallel reduction in lactate production [248]. Ultimately, Herlyn and collegues reported that upon cisplatin or vemurafenib treatment, the appereance of multidrug resistant melanoma cells rely on JARID1B up-regulation.…”
Section: Metabolism and Cancer Therapymentioning
confidence: 99%
“…Along with carbohydrate metabolism, chemotherapy was reported to critically impact lipid-related pathways. In particular, two separate works on breast cancer revealed a significant increase in lipid droplets accumulation and cholesterol biosynthesis upon either doxorubicin [248] or tamoxifen [253]. It is worth noting that the silencing of perilipin, the proteic structural component of lipid droplets, resulted in reduced viability of doxorubicin-resistant breast cancer cells [248].…”
Section: Metabolism and Cancer Therapymentioning
confidence: 99%